2018
DOI: 10.1007/s00066-018-1299-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial orientation of coronary arteries and its implication for breast and thoracic radiotherapy—proposing “coronary strip” as a new organ at risk

Abstract: Our study provides a measure of the radial spread of the coronary arteries, especially from the perspective of breast radiotherapy. We have proposed a new organ at risk (OAR) of coronary strip. This should provide an easy and cost-effective way to delineate the coronary vasculature in breast cancer patients undergoing radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Despite such low mean heart doses, subvolumes such as the heart apex or parts of the LAD can be exposed to much higher doses (Figs. 1 and 2; [41]). In a study conducted by the authors using a modern 3D technique with tangential beams to treat left-sided breast cancer, the mean heart dose amounted 2.1 (0.98–8.3) Gy [42].…”
Section: Value Of Mean Heart Dosementioning
confidence: 99%
“…Despite such low mean heart doses, subvolumes such as the heart apex or parts of the LAD can be exposed to much higher doses (Figs. 1 and 2; [41]). In a study conducted by the authors using a modern 3D technique with tangential beams to treat left-sided breast cancer, the mean heart dose amounted 2.1 (0.98–8.3) Gy [42].…”
Section: Value Of Mean Heart Dosementioning
confidence: 99%
“…Because of changes in dose fractionation (from conventional to hypofractionation) and techniques of RT for breast cancer (from 2D to 3D-CRT/FIF IMRT); dose constraints to be placed for the heart, LAD and lungs and its impact on the cardiac related morbidity and mortality still remains unclear. Although MHD has been the gold standard for prediction of late cardiac effects in the past but recent studies have suggested that reporting doses to the heart substructures such as apical part of left ventricle and LAD may be more relevant [35,36]. Hypofractionation have been reported to result in [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Based on contrast-enhanced CT-angiographies, Munshi et al [ 52 ] proposed a “coronary strip” as a new organ at risk representing the left and the right coronary artery. However, there was considerable variation among the 51 analyzed hearts.…”
Section: Discussionmentioning
confidence: 99%